Regge Poles in Neutron Scattering by a Cylinder - K. V. Protasov; A. Y. Voronin (Advances in High Energy Physics)
We establish asymptotic expressions for the positions of Regge poles for cold neutron scattering on mesoscopic cylinder mirror as well as for the S-matrix residuals. We outline the correspondence between Regge poles and near-surface quasi-stationary neutron states. Such states are of practical importance for studying subtle effects of neutron-surface interaction.